Transformations of structurally stable states of spiral beams subjected to sector perturbations - A.V. Volyar; Ya.E. Akimova (Компьютерная оптика, 2021)
We investigated conditions for the violation of the structural stability of a spiral beam subject to sector perturbations. Based on the method of computer simulation and measurement of mode spectra, we have shown that a spiral vortex beam has a characteristic caustic surface, the intersection of which sharply changes the shape of the Poynting vector streamlines and the total topological charge of the beam. Sector beam perturbation does not almost change the streamline structure up to scale and rotation. We found that perturbation of the beam causes a change in the direction of circulation of streamlines in the region of perturbation, which is caused by the appearance of vortices with negative topological charges. Their contribution to the total energy flow is fractions of a percent. However, such perturbations do not cause changing the OAM in the beam, despite an increase in the number of vortex modes. Nevertheless, the perturbed beam remains only conditionally structurally stable due to the presence of a small fraction of optical currents with opposite circulations.